The Influence of Income and Education Level on Issues of Religion in Romania - Alexandra Georgiana Parasca (CES Working Papers, 2015)
In this research paper the main focus is on religion and how it is influenced by income and education level, how people from different social classes look at religion nowadays. It is a known fact that our income, our education will influence our opinion regarding religion and I analyzed these aspects using a survey carried out by Gallup International for 2014, in Romania. The statistical data shows us clear differences between people with low income and basic education, and people with high income and high education, when it comes to religiosity. Therefore, we can say that income and educational attainment impacts religious belief, but we have to take into consideration that there are exceptions among people and this does not apply to all.
Keywords: Z12; 330; income; education level; religion; Romania